2008
DOI: 10.1177/1049732307311008
|View full text |Cite
|
Sign up to set email alerts
|

A Person-Centered Communication and Reflection Model: Sharing Decision-Making in Chronic Care

Abstract: Shared decision making (SDM) is regarded as an ideal in chronic illness care but is difficult to implement in practice. Communication and reflection play an important role and need further investigation. Using grounded theory, we studied patient-provider interaction in a difficult and advanced area: managing poorly controlled diabetes. A person-centered communication and reflection model was developed, identifying SDM in chronic care to be a question of professionals gaining insight into patients' decisions, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
203
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(218 citation statements)
references
References 35 publications
5
203
0
7
Order By: Relevance
“…Most activities in a CCU are disease-oriented, focused on the patients' symptoms, test results and treatments. The same phenomenon was noted in chronic care, where nurses got stuck in disease-oriented activities, instead of starting from the patient's perspective, and focusing on their understanding of the situation [14]. Workload and lack of time is frequently cited as an argument for not entering into person-centered communication.…”
Section: Critical Interpretation and Reflectionsmentioning
confidence: 80%
See 1 more Smart Citation
“…Most activities in a CCU are disease-oriented, focused on the patients' symptoms, test results and treatments. The same phenomenon was noted in chronic care, where nurses got stuck in disease-oriented activities, instead of starting from the patient's perspective, and focusing on their understanding of the situation [14]. Workload and lack of time is frequently cited as an argument for not entering into person-centered communication.…”
Section: Critical Interpretation and Reflectionsmentioning
confidence: 80%
“…Studies in chronic care indicate that person-centered communication is necessary for shared decision making and to empower patients to take responsibility for their own health [14]. In person-centered communication, the patient's perspective is the foundation for the dialogue, and social, psychological and emotional factors are acknowledged as being equally important as somatic symptoms [2,3,9].…”
mentioning
confidence: 99%
“…First, as an activity of the counsellor, reflection is understood as practices that counsellors use to mirror, dismantle and conceptualize their clients' talk (Brownlee et al, 2009;Miller and Rollnick, 2012;Zoffmann et al, 2008). Second, as an activity of the client, it consists of practices such as autonomous clarifications and reassessments of one's own statements (Zoffmann et al, 2008), or disagreements and explanations (Zapata-Rivera and Greer, 2003). Third, reflection can be understood as joint action of both the counsellor and the client.…”
Section: However There Is Little Knowledge On What Kind Of Action Sementioning
confidence: 99%
“…including both web-based and non-webbased components in the health coaching [2]. Earlier studies on the consultation process revealed that health professionals only have access to a patient's reflections on difficult, personal and relevant subjects in relation to his/her health if the HCP manages to establish an empathic relationship [19].…”
Section: Principal Findingsmentioning
confidence: 99%